A Retrospective Analysis of Maternal Mortality in a Tertiary Care Centre at District Level - Dhundi, Deepika; Kedar, Kshama; Shinde, Nova (Clinical Journal of Obstetrics and Gynecology, 2024)
Background: Maternal mortality is a very sensitive indicator of our health system and services. Epidemiological data about maternal mortality is a vital requirement in every setting not only to design interventional programs but also to identify gaps in the existing structures, to reduce the ratio favorably. This study was an attempt to shed light on the mortality rate in our hospital, to analyze the epidemiological aspects, causes of maternal mortality, and types of delay, and to suggest recommendations for improvement. Methods: A retrospective study was done at a tertiary care center at the district level from January 2022 to December 2022. Demographic data and details of selected parameters were obtained from maternal death review forms and case records. Data analyzed and presented. Results: The majority of the maternal deaths could be attributed to direct obstetric causes like Eclampsia (29.41%), Pre-eclampsia (20.59%), and anemia (20.59%) followed by hemorrhage (14.71%), and septicemia (11.76%). Medical conditions contributing to death included liver disorders (5.8%), COVID-19 infection (5.8%), and cardiac disorders (2.9%). Conclusion: It is evident that the maternal mortality ratio is significantly high, with a majority of the deaths occurring due to avoidable causes. Leading contributory factors were due to delay in seeking help or delay in referral. High-risk cases must be identified at the earliest and referred to higher centers for management from the first trimester itself. Generating awareness among the common public and counseling the gravidas and their caretakers throughout pregnancy is equally important to prevent maternal mortality and near-miss cases.